Sidestream cigarette smoke toxicity increases with aging and exposure duration - Schick, Suzaynn (BMJ Group, 2006)
OBJECTIVES: To determine the effects of aging on the toxicity of sidestream tobacco smoke, the complex chemical mixture that enters the air from the lit end of burning cigarettes and constitutes the vast bulk of secondhand smoke. DESIGN: Statistical analysis of data from controlled experimental exposures of Sprague Dawley rats to fresh and aged (for more than 30 minutes) sidestream smoke for up to 90 days followed by histological sectioning of the respiratory epithelium. The data were obtained from a series of experiments conducted at Philip Morris' formerly secret INBIFO (Institut für Biologische Forschung) laboratory in Germany. RESULTS: Using total particulate material as the measure of smoke exposure, aging sidestream cigarette smoke for at least 30 minutes increases its toxicity fourfold for 21 day exposures and doubles the toxicity for 90 day exposures, relative to fresh sidestream smoke. CONCLUSIONS: These results help explain the relatively large biological effects of secondhand smoke compared to equivalent mass doses of mainstream smoke.